2016
DOI: 10.1051/0004-6361/201525976
|View full text |Cite
|
Sign up to set email alerts
|

Warm ionized gas in CALIFA early-type galaxies

Abstract: Context. The morphological, spectroscopic, and kinematical properties of the warm interstellar medium (wim) in early-type galaxies (ETGs) hold key observational constraints to nuclear activity and the buildup history of these massive, quiescent systems. High-quality integral field spectroscopy (IFS) data with a wide spectral and spatial coverage, such as those from the CALIFA survey, offer an unprecedented opportunity for advancing our understanding of the wim in ETGs. Aims. This article centers on a 2D invest… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
126
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 108 publications
(134 citation statements)
references
References 102 publications
8
126
0
Order By: Relevance
“…However, as pointed out in Papaderos et al (2013) and Gomes et al (2016) (see also CGP16), standard BPT classification diagnostics become inapplicable in the case of virtually gas-evacuated galaxies where the bulk of the Lyman continuum radiation from an AGN eventually escapes without locally producing detectable optical line emission. This, together with dilution of nuclear emission-line EWs by the stellar component along the line of sight, may readily prevent detection of accretion-powered nuclear activity in an early-type galaxy (Papaderos et al 2013;Gomes et al 2016), which is then classified as retired/passive and included in automated PSS studies. The same may obviously apply to old classical bulges, many of which show faint nebular emission despite hosting a super-massive black hole whose accretion-powered energy release may result in significant contamination of the optical spectrum by an AGN PL component.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as pointed out in Papaderos et al (2013) and Gomes et al (2016) (see also CGP16), standard BPT classification diagnostics become inapplicable in the case of virtually gas-evacuated galaxies where the bulk of the Lyman continuum radiation from an AGN eventually escapes without locally producing detectable optical line emission. This, together with dilution of nuclear emission-line EWs by the stellar component along the line of sight, may readily prevent detection of accretion-powered nuclear activity in an early-type galaxy (Papaderos et al 2013;Gomes et al 2016), which is then classified as retired/passive and included in automated PSS studies. The same may obviously apply to old classical bulges, many of which show faint nebular emission despite hosting a super-massive black hole whose accretion-powered energy release may result in significant contamination of the optical spectrum by an AGN PL component.…”
Section: Discussionmentioning
confidence: 99%
“…The code Starlight is widely used (e.g. Mateus et al 2006;Stasińska et al 2008;Cid Fernandes et al 2010Kehrig et al 2012;Benítez et al 2013;Papaderos et al 2013;Cid Fernandes et al 2014;Stasińska et al 2015; 2 Starlightv04: http://astro.ufsc.br/starlight/ Gomes et al 2016) and can be regarded as a good representative of the state of the art. It is important to bear in mind the main objective of this work is to quantify potential biases on fundamental physical properties of active galaxies estimated with purelystellar PSS that might rise owing to the introduction of a simple AGN model, as in Ciesla et al (2015).…”
Section: Application Of Population Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…For simplicity, the galaxy is constructed such as to display a constant age gradient ∇t = −0.5 Gyr/kpc, which imposes a maximum radius as a function of lookback time of R max (t) = (t 0 − t)/|∇t|, where t 0 is the galaxy formation lookback time. For the adopted model, the galaxy grows radially at a constant speed v ∼ 2km s −1 , and when it attains R max = 20 kpc (at z ∼ 0.3), the linear growth ceases, yielding a typical present-day ETG radius (e.g., Gomes et al 2015a). The Friedmann-Robertson-Walker cosmology with H 0 = 70 km s −1 Mpc −1 , Ω m = 0.3 and Ω Λ = 0.7 was adopted, yielding 13.52 Gyr for the age for the Universe.…”
Section: Inside-out Galaxy Formation and Associated Aperture Effectsmentioning
confidence: 99%
“…For example, Kaviraj et al (2008) found that 10−15% of the stellar mass (M ) in these systems has been built in a declining SF process since z 1, a conclusion that appears to be in line with the small fraction (∼5.7%) of blue ETGs in the local Universe with estimated SF rates (SFRs) of between 0.5 and 50 M /yr (Schawinski et al 2009). It is also noteworthy in this context that spatially resolved studies of individual ETGs indicate an outward-increasing luminosity contribution from young-to-intermediate-age stellar populations (e.g., Fang et al 2012;Gomes et al 2015a). …”
Section: Introductionmentioning
confidence: 99%